PERANCANGAN STARTUP PLATFORM MANAJEMEN PELAPORAN SEKOLAH KEPADA ORANG TUA/WALI SISWA DENGAN PENDEKATAN DESIGN THINKING - Rohwana, Ulir; Irawan, Mohammad Isa (Universitas Airlangga, 2024)
This research aimed to develop a startup for a school-to-parent reporting platform, inspired by the vast potential of Indonesia's education business market. By adopting a design thinking approach, this research developed suitable business models. The design thinking process involves five stages: empathize, define, ideate, prototype, and test. The empathize stage involved observations and interviews to understand user perspectives, namely school administrators and parents. In the define stage, user problems were formulated using Point of View (POV) techniques, followed by SWOT and competitor analyses to identify solutions and opportunities. Next, in the ideate stage, ideas were gathered through brainstorming sessions and structured into a Business Model Canvas. In the prototyping phase, UI/UX designs were visualized and business models were drafted. Finally, platform testing was conducted in a school to evaluate its suitability for user needs and obtain feedback before scaling up. The testing showed that the design thinking approach was well-received by users in designing the school reporting platform startup in terms of technological solutions and business models. This research contributes to designing a user-centric startup with viable business models, increasing market acceptance, and gaining substantial market share in Indonesia's education industry.